If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -8x = 12 Combine like terms: 2x + -8x = -6x -6x = 12 Solving -6x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-6'. x = -2 Simplifying x = -2
| 4(2y-1)+3=3y-1 | | 4x+(-3)=-5 | | 2.5-2y=5.5 | | 11x+-2=-1 | | (5w^2-10w-175)/(w^2-5w-14) | | 585=X*4.78723839954/4.74341649025 | | 4x+13=-1 | | y+2/3y | | 4x+(-8)=-2 | | 5x+(-8)=-2 | | 2x^2-8x+3=x^2-3x-3 | | 8x-11(x-2)=45 | | 585=(X*3.5^1.25)/22.5^0.5 | | 2/3-x=5/6 | | (4y^2)-1=0 | | 3x^2-5x+7=x^2+2x+1 | | 5.4(4+2x)-7.6=14 | | 6+x/6=-1.68 | | 7/6x-7=10/3x+10 | | 9=19-1y | | 5+a/6=8 | | 4(x-3)=3x-7[4] | | 8y+5x=0 | | 16x^2-24x-5=0 | | 9y^2-36=0 | | 6+1/5x=2 | | 1/2w=-9 | | 3/-8*2/7*-3 | | 36/0.04 | | 8x^2+77x+45=0 | | Ln(lne)=4lnx | | 4/9*7*-3/-8 |